Adsorption Study and Removal of Basic Fuchsin Dye from Medical Laboratory Wastewater Using Local Natural Clay - Fuad Hama Sharif Radha; Dler M. S. Shwan; Stephan Kaufhold (Adsorption Science & Technology)
Local natural clay from Sulaimani zone-Takiya (TKC), Kurdistan Region of Iraq, was characterized and used for the removal of basic fuchsin (BF) dye from laboratory bacterial wastewater. The characterization of the adsorbent was carried out with XRD, XRF, and FT-IR. The clay sample was dominated by vermiculite. Adsorption tests under different conditions of contact time, pH of the solution, temperature, initial dye concentration, and adsorbent amount were performed to analyze the effect of various experimental parameters. Equilibrium time was reached within 180 minutes, and maximum BF adsorption was achieved at pH 6.8 at a temperature ranging from 20 to 50°C. The experimental data fitted the pseudo-second-order kinetic model, with the activation energy of 22.68 kJ·mol-1. Adsorption isotherms could be well-fitted by the Langmuir isotherm model. The thermodynamic parameters such as ΔG°, ΔH°, and ΔS° were determined, and the negative values of ΔG° indicated that adsorption was spontaneous at all temperatures. Furthermore, the values of ΔH° indicated an endothermic reaction. Wastewater contaminated by BF dye from the bacterial laboratory was collected (BF concentration: 160 mg·L-1) and treated by TKC. The resulting concentration of BF after adsorption was 4.76 mg·L-1. The maximum amount of dye adsorbed is about 149.2 mg/g or 0.44 mmol/g, which is close to the range of the cation exchange capacity (CEC) value of the vermiculite which indicated that cation exchange was the dominant adsorption mechanism.